Citizen or consumer? Contrasting Australia and Europe's data protection policies - James Meese; Punit Jagasia; James Arvanitakis (Internet Policy Review, 2019)
This paper examines how data access and transfer rights are conceptualised in the European Union and Australia. The study discusses the planned introduction of a Consumer Data Right (CDR) to Australia and contrasts it to comparable developments in European law. We then assess the broader reform moments around data (which these various data access and transfer rights form a part of), that have occurred in each jurisdiction. The paper shows that Europe has placed an increasing value on protecting the fundamental rights of citizens, whereas Australia has taken a more neoliberal approach to data, only granting individuals rights in the context of the market.
Keywords: 300; Data access; General Data Protection Regulation; Consumer Data Right; Privacy; Data protection